Helicoidal multi-lamellar features of RGD-functionalized silk biomaterials for corneal tissue engineering - Gil, Eun Seok (2010)
RGD-coupled silk protein-biomaterial lamellar systems were prepared and studied with human cornea fibroblasts (hCFs) to match functional requirements. A strategy for corneal tissue engineering was pursued to replicate the structural hierarchy of human corneal stroma within thin stacks of lamellae-like tissues, in this case constructed from scaffolds constructed with RGD-coupled, patterned, porous, mechanically robust and transparent silk films. The influence of RGD-coupling on the orientation, proliferation, ECM organization, and gene expression of hCFs was assessed. RGD surface modification enhanced cell attachment, proliferation, alignment and expression of both collagens (type I and V) and proteoglycans (decorin and biglycan). Confocal and histological images of the lamellar systems revealed that the bio-functionalized silk human cornea 3D constructs exhibited integrated corneal stroma tissue with helicoidal multi-lamellar alignment of collagen-rich and proteoglycan-rich extracellular matrix, with transparency of the construct. This biomimetic approach to replicate corneal stromal tissue structural hierarchy and architecture demonstrates a useful strategy for engineering human cornea. Further, this approach can be exploited for other tissue systems due to the pervasive nature of such helicoids in most human tissues.